2017
DOI: 10.4103/meajo.meajo_17_17
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for choroidal neovascularization associated with angioid streaks: Long-term results

Abstract: PURPOSE:The purpose of the study was to evaluate the long-term efficacy and safety of intravitreal bevacizumab (IVB) in the treatment of choroidal neovascularization (CNV) secondary to angioid streaks (AS).MATERIALS AND METHODS:Noncomparative, interventional retrospective case series involving ten patients (15 eyes) with a minimum follow-up of 25 months following IVB for AS-associated CNV. Demographic and clinical details at baseline and during follow-up were collected from patient records. Detailed clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…10 Many studies have confirmed the efficacy of intravitreal anti-VEGF therapy on CNV secondary to ASs. [13][14][15][16][17][18][19][20]27 Intravitreal injections have improved the functional outcome of these patients by controlling CNV activity. The French PIXEL study has shown that the mean VA was maintained at one year with treatment with 0.5 mg of ranibizumab and it remained stable for up to four years.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many studies have confirmed the efficacy of intravitreal anti-VEGF therapy on CNV secondary to ASs. [13][14][15][16][17][18][19][20]27 Intravitreal injections have improved the functional outcome of these patients by controlling CNV activity. The French PIXEL study has shown that the mean VA was maintained at one year with treatment with 0.5 mg of ranibizumab and it remained stable for up to four years.…”
Section: Discussionmentioning
confidence: 99%
“…27 Since the advent of anti-VEGF, many groups have published their experience on the response of ASrelated CNV to antiangiogenic molecules. 14,15,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Most of the studies showed that anti-VEGF agents are effective to stabilize, and in a minority of cases to improve, the visual acuity at long-term follow-up, irrespective of the administered molecule (i.e. bevacizumab, ranibizumab or aflibercept).…”
Section: Discussionmentioning
confidence: 99%
“…10 In Lekha et al 11 study showed that recurrence was observed in 73.33% eyes after 5.60 bevacizumab injection over 57.33 months follow-up. 11 They concluded that more effective options are needed to reduce risk of recurrence. 11 Similarly, we observed sharp changes both significant decrease and increase in patient's visual acuity during the 5 bevacizumab injections in 2.5 years follow-up and first achieved positive anatomic and functional responses could not preserved, patient had complained of severe image distortion.…”
Section: Discussionmentioning
confidence: 99%